Multicultural Discourse in Works by Barbara Frishmuth: Crossing the border between East and West (by Example of Novel “The Disappearance of the Shadow in the Sun”) - L. V. Trofimova (Научный диалог)
The works by Barbara Frischmuth - known master of contemporary German-language literature - are considered. Her works are in tune with time, so in her works it is easy to find the “problematic theme” of our time. It is shown that Barbara Frischmuth creates highly individual art world, she includes, following Austrian tradition, a fantastic item and philosophical reflections in the narration. It is indicated that the author of numerous novels and books for the younger generation relates to the questions of the relationship between East and West in her works. It is noted that Barbara Frischmuth is able not only to convey to the reader her ideas, but to force critical thinking about life. The author explores the features of Barbara Frischmuth’s multiculturalism as an aspect of tolerance, that consists in the possibility of parallel coexistence and mutual enrichment of cultures, by the material of the novel “The Disappearance of the Shadow in the Sun” (“Das Verschwinden des Schattens in der Sonne,” 1971). The relevance of the study is dictated by the need of rethinking of the relationships between representatives of different religious faiths (Islam and Christianity) that have been forming in European society for decades, taking into account the changed geopolitical situation. The author gives a generalized characteristic of “multiculturalism” and considers the work of the Austrian writer in this context.